The aggregation challenge - Macartan Humphreys; Alexandra Scacco (World Development, 2020)
Banerjee, Duflo, and Kremer have had an enormous impact on scholarship on the political economy of development. But as RCTs have become more central in this field, political scientists have struggled to draw implications from proliferating micro-level studies for longstanding macrolevel problems. We describe these challenges and point to recent innovations to help address them.
Keywords: 330